(untitled) (World Science, 2020)
Macroanatomy, topography of the submandibular salivary glands in rats, the size and mechanisms of functioning, are determined by the characteristics of the structure of the skull and cervical area, and the horizontal position of the animal body and features of the functional purpose of the glands. Salivary glands ensure the consistency of homeostasis not only in the oral cavity, but also in the upper gastrointestinal tract, performing the primary enzymatic processing of food, helping the passage of food to the esophagus. Apparently, there are no other organs that perform as many functions (secretory, secretory, excretory, secretory) and have such a significant impact on the condition of the organism, oral cavity and digestive system as a whole. This publication demonstrates microstructures characteristics of submandibular salivary gland of rats.